2013
DOI: 10.1037/a0028046
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress and posttraumatic growth and their relationship to coping and self-efficacy in Northwest Australian cyclone communities.

Abstract: The main focus of disaster research conducted to date has been on providing insights into the negative consequences of experiencing a serious threat or adversity. The present study extends this research endeavour by investigating the positive post-trauma resiliency experiences of 512 survey respondents living in four cyclone prone communities in Northwest Australia. The findings reveal that disaster stress is often accompanied by disaster growth and, thus, provides an alternative resilience-based way of viewin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 67 publications
6
43
1
2
Order By: Relevance
“…Reflecting this last category, Tedeschi and Calhoun (1996) proposed the concept of PTG, which they defined as 'positive change that occurs as a result of the struggle with highly challenging life crises' (Tedeschi & Calhoun, 2004, p.1). Since then, a wealth of studies have corroborated the concept, with studies invariably finding that 'a majority' (percentages vary) of people suffering trauma experience some degree of PTG, with the trauma in question ranging from illness like cancer (e.g., Koutrouli, Anagnostopoulos, & Potamianos, 2012) to natural disasters such as cyclones (Pooley, Cohen, O'Connor, & Taylor, 2013).…”
Section: Diagnostic and Statistical Manual Of Mental Disorder (Dsm-iimentioning
confidence: 91%
“…Reflecting this last category, Tedeschi and Calhoun (1996) proposed the concept of PTG, which they defined as 'positive change that occurs as a result of the struggle with highly challenging life crises' (Tedeschi & Calhoun, 2004, p.1). Since then, a wealth of studies have corroborated the concept, with studies invariably finding that 'a majority' (percentages vary) of people suffering trauma experience some degree of PTG, with the trauma in question ranging from illness like cancer (e.g., Koutrouli, Anagnostopoulos, & Potamianos, 2012) to natural disasters such as cyclones (Pooley, Cohen, O'Connor, & Taylor, 2013).…”
Section: Diagnostic and Statistical Manual Of Mental Disorder (Dsm-iimentioning
confidence: 91%
“…Their results broadly showed that stress is negatively correlated with self-efficacy. More specifically, the results revealed that individuals who engaged in emotion-focused coping had lower self-efficacy levels (Pooley et al, 2012). The current study will explore the relationships among academic self-efficacy, stress coping skills, and academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Posttraumatic growth also appears to be a global phenomenon. In 2012 alone, psychologists have published reports of posttraumatic growth among Turkish university students (Arikan & Karanci, 2012), Chinese earthquake victims (Qian, Yang, Li, Xu, & Wang, 2012), Chinese cancer patients (Tong et al, 2012), tsunami relief volunteers in India (Bhushan & Kumar, 2012), Japanese youth (Taku, Kilmer, Cann, Tedeschi, & Calhoun, 2012) and individuals living in Northwest Australian cyclone-prone communities (Pooley, Cohen, O'Connor, & Taylor, 2012).…”
Section: Defining Positive Adaptationmentioning
confidence: 99%